Geotechnical Stability Assessment and Soil Improvement Recommendations using Soil Grouting and Drainage Tunnels (Case study: Retaining wall displacement at a transmission tower site) - Khoeri, Heri; Pradana, Roberto; Isvara, Wisnu; Irwanto, Rachmad (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
The detection of a retaining wall displacement in early 2023 at one of the DD6+12 transmission tower sites raised concerns about the tower's stability, potentially leading to structural failure. A comprehensive assessment was conducted on the tower's verticality, retaining wall displacement, subsurface conditions, and soil properties around the tower area. The assessment results revealed a linear inclination of the transmission tower from the base to the top, with a deflection at the top of approximately ±20 cm to the south and ±7 cm to the west. With this condition, some structural elements reached a stress-to-permitted stress ratio of 0.91. Although still within allowable limits, without soil stabilization, it is at risk of structural failure. GPR scan results showed differences in foundation dimensions compared to the as-built drawings and identified cavities filled with water beneath the ground surface due to poor drainage, resulting in a safety factor of 1.088, whereas the required safety factor is 1.5. This condition caused the retaining wall displacement. Recommendations including constructing drainage tunnels upstream, soil grouting, installing wheep holes in the retaining walls, and adding secant piles would increase the safety factor to 1.988.